Teachers' Curriculum Stories: Perceptions and preparedness to enact change. Issue 13 (9th November 2016) - MacDonald, Abbey; Barton, Georgina; Baguley, Margaret; Hartwig, Kay
Abstract: Within the specific context of The Australian Curriculum: The Arts, this paper explores how teachers of the Arts and teacher educators encounter and enact curriculum change. Adopting Ewing's notion that curriculum is a complex web of varying stories and storylines that are impacted on by teachers' underlying philosophy, we suggest that Arts teachers embrace the intent behind The Australian Curriculum: The Arts . This paper unearths and explores insights gleaned from teachers looking inward and reflecting on their own personal curriculum journeys. The learning dimensions of conceptualising, experimenting and developing, reflecting, resolving and communicating are applied to investigate the implementation of the new curriculum. This article shares data from a number of Arts teachers' interviews with the authors in relation to their thoughts on the implementation of the new curriculum. Two key themes emerged from these interviews, these being navigating challenges and the implications of personal attributes in encountering and enacting change. Interestingly, a number of qualities associated with Arts practitioners such as creative and lateral thinking, resilience and flexibility emerge as significant contributing factors in regard to how teachers encounter, enact and become curriculum change.